Macronutrient status and yield stability of arecanut (Kahikuchi) under integrated nutrient management practice in Assam - Paul, S.C.; Acharya, G.C.; Hussain, M.; Ray, A.K.; Sit, A.K. (Journal of Plantation Crops, 2015)
A long term field experiment was carried out in clay-loam soil at ICAR-CPCRI, Kahikuchi campus, Guwahati, Assam during 2000-2012 with arecanut variety Kahikuchi with seven nutrient combinations. The treatments included control (T1), 100 per cent vermicompost (T2), 200 per cent vermicompost (T3), 100 per cent chemical fertilizer (T4), 50 per cent vermicompost + 50 per cent chemical fertilizer (T5), 1/3rd vermicompost + 2/3rd chemical fertilizer (T6) and 2/3rd vermicompost + 1/3rd chemical fertilizer (T7). The treatment T7 produced highest fresh ripened arecanut yield of 16.7 kg i.e., about 3.6 kg dry chali per palm. Positive correlations were obtained between yield of arecanut and soil available N, P, K content. Significant and positive correlation was found between leaf N, P, K and available N, P, K content in surface and sub-surface soil. Available N, P and K content increased over the year under nutrient applied plot that reflected in yield of arecanut. The average yield in various treatments followed in the order of T7 > T5 = T6 > T2 = T3 > T4 > T1. The application of targeted, sufficient and balanced quantities of organic and inorganic fertilizer will be the need of the hour to make nutrients available for higher yield, soil fertility maintenance and agricultural sustainability without polluting environment.